Rancang bangun tirai otomatis menggunakan sensor cahaya dan remote control (A design of automatic blinds using a light sensor and remote control) - Desvita Roza; - Hufri (Department of Physics – Universitas Negeri Padang UNP, 2020)
The development of science and technology that is increasingly advanced is widely used by humans to meet human needs. This rapid technological development is marked by the number of equipment that has been created and operated both manually and automatically. Utilization of an automatic control system in the context of smarh home can be applied to the curtain and light media that exist in every home. The purpose of this study is to determine the performance specifications and design specifications of an automatic curtain using a light sensor and remote control.This research is included in engineering research. This study explains the specifications of performance and specifications for automatic curtain design. Performance specifications describe the functions of automatic curtain tool builders, while design specifications explain the accuracy and accuracy of the tools. The measurement technique is done directly and indirectly. Direct measurements are carried out on the voltage value, while indirect measurements are carried out by analyzing the accuracy and accuracy of the automatic curtain tool. The sensor used is the LDR sensor. The results of the study of performance specifications and design specifications. First, the performance specifications of the automatic curtain consist of the LDR sensor, remote control, curtain drive, and electronic circuit builder of the automatic curtain system. The LDR sensor used is the LDR sensor with a maximum resistance of 50kΩ. The second result, the results of the design specifications of this study consisted of accuracy and accuracy. The accuracy value of the automatic curtain tool is 99.16% and the accuracy value is 98.98%